Autoimmune liver disease in a toddler - Kaushik Barot; Sejal Ramavat; Vivek Tarsariya (Indian Journal of Child Health, 2021)
Autoimmune liver disease (AILD) is a rare cause of chronic liver disease in toddlers. We report a 2.5-year-old child who presented with recurrent episodes of jaundice. The child was diagnosed to have AILD type 2. He was successfully treated and is doing well on 5 years follow-up.